2007
DOI: 10.1016/j.visres.2007.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spatial pooling and attention in saccadic and perceptual tasks

Abstract: Saccades aimed at spatially extended targets land reliably at central locations determined by pooling information across the target shape [Melcher, D., & Kowler, E. (1999). Shape, surfaces and saccades. Vision Research, 39, 2929-2946; Vishwanath, D., & Kowler, E. (2003). Localization of shapes: Eye movements and perception compared. Vision Research, 43, 1637-1653]. Previous findings of saccadic errors when attempting to look at a target in the midst of distractors encouraged suggestions that pooling occurs ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Since resolution decreases with eccentricity from fixation, the optimal gaze position is the centroid of the selected spatial regions, a prediction supported by the finding that saccade size correlates better with the distance of the centroid of selected targets than the centroid of targets plus intervening distractors30. By comparing fixation to multi-target geometries which yield different centroid predictions for the three different models of spatial selection (Fig.…”
mentioning
confidence: 85%
“…Since resolution decreases with eccentricity from fixation, the optimal gaze position is the centroid of the selected spatial regions, a prediction supported by the finding that saccade size correlates better with the distance of the centroid of selected targets than the centroid of targets plus intervening distractors30. By comparing fixation to multi-target geometries which yield different centroid predictions for the three different models of spatial selection (Fig.…”
mentioning
confidence: 85%
“…), but more recent work has shifted the responsibility for averaging to the operation of a selective filter that was not given either the time, or the visual cues, to find the target before the saccade was launched. This shift in view was prompted by findings that saccades became more accurate (less influence of the surrounding non-targets) when more time was allowed for target selection to occur (Ottes, Van Gisbergen & Eggermont, 1985; CöeffĂ© & O’Regan, 1987; Cohen, Schnitzer, Gersch, Singh & Kowler, 2007), or when cues or instructions were given to signal where the saccade should land (He & Kowler, 1989, 1991; Findlay & Blythe, 2009). These considerations show that center-of-gravity saccades are no different from any saccade: they direct the line of sight to the attended region.…”
Section: Saccadesmentioning
confidence: 99%
“…Previous work found that when participants made saccades to a group of peripheral targets, the saccadic endpoint landed near the center of the target group, both when the targets were alone and amidst differently colored distractors (Cohen, Schnitzer, Gersch, Singh, & Kowler, 2007; McGowan, Kowler, Sharma, & Chubb, 1998). However, unlike the stationary target groups employed previously, we have investigated eye movements during MOT in which targets move and can only be distinguished from distractors via accurate attentive tracking.…”
Section: Introductionmentioning
confidence: 99%